2020
DOI: 10.21608/mjmr.2022.221015
|View full text |Cite
|
Sign up to set email alerts
|

Clinical usefulness of serum ferritin level in patients with fatty liver

Abstract: Background: Non-alcoholic fatty liver disease (NAFLD) is one of the most common causes of chronic liver disease worldwide. Recently several parameters, such as serum ferritin, have emerged as possible predictors for the severity of NAFLD and insulin sensitivity. We aimed to investigate the value of serum ferritin level as a useful biomarker for the prediction of disease severity in patients with NAFLD. Methods: This was a prospective cross sectional study in which demographic, clinical and laboratory data of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Regarding, serum ferritin levels' clinical utility in fatty liver patients, according to Mohammed et al (20) , hyperferritinemia is prevalent in NAFLD patients, although the degree of serum ferritin increases does not indicate the stage of the underlying condition. Ferritin has been demonstrated to be a predictor of advanced fibrosis, obesity, IR, and cardiovascular disease have all been linked to hyperferritinemia, diseases connected to NAFLD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding, serum ferritin levels' clinical utility in fatty liver patients, according to Mohammed et al (20) , hyperferritinemia is prevalent in NAFLD patients, although the degree of serum ferritin increases does not indicate the stage of the underlying condition. Ferritin has been demonstrated to be a predictor of advanced fibrosis, obesity, IR, and cardiovascular disease have all been linked to hyperferritinemia, diseases connected to NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Ferritin has been demonstrated to be a predictor of advanced fibrosis, obesity, IR, and cardiovascular disease have all been linked to hyperferritinemia, diseases connected to NAFLD. It has been suggested that serum ferritin, but not serum iron, transferrin saturation, or hepatic iron concentration, is greater in cases with severe fibrosis compared to moderate fibrosis, but not in individuals with steatosis or inflammation, and that it can in an independent manner predict extensive fibrosis (20) . Similarly, according to Kowdley and colleagues (21) , there is a direct link between elevated blood ferritin levels and a higher risk of progressive fibrosis in NAFLD.…”
Section: Discussionmentioning
confidence: 99%